2002
DOI: 10.1021/ja027660j
|View full text |Cite
|
Sign up to set email alerts
|

From Chiral Counterions to Twisted Membranes

Abstract: In membranes, the chirality of the amphiphile constituents is sometimes expressed at a supramolecular scale of nanometers or micrometers. We have recently reported that membranes of nonchiral dicationic n-2-n amphiphiles can also be chirally twisted upon interacting with chiral tartrate counterions. Here, we demonstrate that the mechanism of the chiral induction by counterions involves specific anion-cation recognition and the induction of conformationally labile chirality in the cations. Single-crystal X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 37 publications
5
123
0
Order By: Relevance
“…τ m is the geodesic torsion along the unit vector m at some point. Here m represents the projected direction of the lipid molecules in the experiments [2,3,4,5,6,7,8] and chiral tartrate counterions in the experiment [9,10] on the membrane surface, respectively. If we take a righthanded orthonormal frame {e 1 , e 2 , e 3 } with e 3 being the normal vector of the membrane as shown in Fig.…”
Section: Free Energy Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…τ m is the geodesic torsion along the unit vector m at some point. Here m represents the projected direction of the lipid molecules in the experiments [2,3,4,5,6,7,8] and chiral tartrate counterions in the experiment [9,10] on the membrane surface, respectively. If we take a righthanded orthonormal frame {e 1 , e 2 , e 3 } with e 3 being the normal vector of the membrane as shown in Fig.…”
Section: Free Energy Densitymentioning
confidence: 99%
“…Since tubules were fabricated successfully from chiral lipid molecules, chiral lipid structures have attracted much experimental attention [1,2,3,4,5,6,7,8,9,10]. Most of chiral structures in experiments are self-assembled from DC 8,9 P C which is a typical chiral molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, unsaturated oleic moiety appears to be critical in nanotube formation. The literature survey [29][30][31][32][33] reveals that tube-forming self-assembled molecular species requires unsaturation in the lipophilic moiety although, the evidence is limited. A recent study [34,35] of cardanol-based glycolipid also shows that glycolipid with unsaturated chain self-assembled into coiled or tubular structures by non-parallel chiral packing due to kink into alky chain's structure expressed by the cisdouble bond of the monoene, while the saturated analogue self-assembled into twisted fibers through parallel chiral packing.…”
Section: Resultsmentioning
confidence: 99%
“…chirality, on assembled systems can be profound. It has been reported that chirality plays critical roles in assembling processes taking place on surfaces and interfaces, in liquid crystalline phase, and in the formation of supramolecular polymers and gels [38,39]. Shinkai and coworkers synthesized nineteen cholesteryl derivatives containing a variety of azobenzene moieties coupled to (S)-and (R)-C-3 of a steroidal moiety through an ester linkage.…”
mentioning
confidence: 99%